(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Road traffic accident (RTA) is a growing public health problem worldwide. It is responsible for greatest number of injuries and fatalities by killing around 1.2 million people each year and injuring 50 million who occupy 30-70% of orthopedic beds in developing countries hospitals. Pedestrians are the most common victims of RTAs. Objective: To find out the epidemiological factors and pattern of road traffic injury among pedestrians admitted at selected tertiary level referral hospitals in Dhaka City for getting necessary treatment. Materials and Methods: This descriptive type of cross sectional study was done during December 2015 to June 2016 at four tertiary level referral hospitals in Dhaka. A total of 197 pedestrian patients were selected by purposive and convenient method of sampling. The primary data was collected from the patients after their discharge from hospital by face to face Exit interview using a pre tested semistructured questionnaire. Results: Among 197 pedestrian victims interviewed; 129(65.48%) were male and 68(34.52%) female. Maximum accidents took place on city main roads 93(47.21%), followed by internal roads 93(47.21%), maximum accidents occurred at day time 87(44.16%), followed by evening 49(24.87%). Regarding vehicles, highest number of accidents were caused by buses 63(31.97%), followed by mini bus 42(21.32%). Highest incidence of injuries was observed among the age group 21 to 30 yrs 81(41.12%), 168( 85.27%) reported that they had been knocked down by the vehicles while crossing the roads (hit and run injury), 24(12.18%) were injured by motor cycles moving at a speed illegally on the footpath, 56(28.42%) people fall on ground due to faulty roads and potholes, open manhole cover followed by vehicle’s accident. Majority of victims 136(69.03%) were from earning group below 15,000 taka per month, most of the victims 155(78.68%) never used foot over bridge,168(85.27%) person faced difficulty while walking through footpath due to piling of construction materials, selling items of neighboring shops etc, 127(64.47)% were using mobile phone while crossing the road or walking through it. All the research samples had multiple abrasion and bruise all over the body, 164(83.25%) had lacerations in different body area, 85(43.14%)%) had fracture of upper limb bones, 69(35.03%)had fracture of lower limb bones . Conclusion: The incidence and severity of injury of road accident can be prevented by motivation of public, strict application of traffic rules and proper training of drivers. More scientific research on road traffic injury are needed in future. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 3-7